The Role of Tides in Ocean‐Ice Shelf Interactions in the Southwestern Weddell Sea. Issue 6 (11th June 2020) - Hausmann, U.; Sallée, J.‐B.; Jourdain, N. C.; Mathiot, P.; Rousset, C.; Madec, G.; Deshayes, J.; Hattermann, T.
Abstract: To investigate the role of tides in Weddell Sea ocean‐ice shelf melt interactions, and resulting consequences for ocean properties and sea ice interactions, we develop a regional ocean‐sea ice model configuration, with time‐varying ocean boundary and atmospheric forcing, including the deep open ocean (at 2.5–4 km horizontal resolution), the southwestern continental shelf (≈2.5 km), and the adjacent cavities of eastern Weddell, Larsen, and Filchner‐Ronne ice shelves (FRIS, 1.5–2.5 km). Simulated circulation, water mass, and ice shelf melt properties compare overall well with available open ocean and cavity observational knowledge. Tides are shown to enhance the kinetic energy of the time‐varying flow in contact with the ice shelves, thereby increasing melt. This dynamically driven impact of tides on net melting is to almost 90% compensated by cooling through the meltwater that is produced but not quickly exported from regions of melting in the Weddell Sea cold‐cavity regime. The resulting systematic tide‐driven enhancement of both produced meltwater and its refreezing on ascending branches of, especially the FRIS, cavity circulation acts to increase net ice shelf melting (by 50% in respect to the state without tides, ≈50 Gt yr −1 ). In addition, tides also increase the melt‐induced FRIS cavity circulation, and the meltwater export by the FRIS outflow. Simulations suggest attendant changes on the open‐ocean southwestern continental shelf, characterized by overall freshening and small year‐round sea ice thickening, as well as in the deep southwestern Weddell Sea in the form of a marked freshening of newly formed bottom waters. Key Points: Ocean/sea‐ice/tide/interactive ice‐shelf melt model simulates near‐observed Weddell Sea gyre, continental‐shelf, and cavity water masses Tides amplify basal melt‐refreeze pattern, raising net melt by 50%, associated with enhanced time‐varying kinetic energy at the ice base Impacts of additional meltwater production on Weddell continental shelf sea ice and newly formed bottom water properties are suggested